2021
DOI: 10.32872/cpe.5501
|View full text |Cite
|
Sign up to set email alerts
|

Item response model validation of the German ICD-11 International Trauma Questionnaire for PTSD and CPTSD

Abstract: Background In the 11th revision of the International Classification of Diseases (ICD-11) posttraumatic stress disorder (PTSD) and the complex variant (CPTSD) were newly conceptualised. The International Trauma Questionnaire (ITQ) was developed as a brief self-report measure to screen for both disorders. The English original version has been rigorously tested and presents convincing psychometric properties. The aim of the current study was to validate the German version by means of item response the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…For both scales, reliability was good with α = 0.84 for the PTSD scale and α = 0.88 for the cPTSD scale ( 53 ). The German version has been validated in a representative population-based sample and can be used for research and clinical practice ( 54 ). In our sample, good internal consistency was observed for both the PTSD (α = 0.89) and cPTSD scale (α = 0.87).…”
Section: Methodsmentioning
confidence: 99%
“…For both scales, reliability was good with α = 0.84 for the PTSD scale and α = 0.88 for the cPTSD scale ( 53 ). The German version has been validated in a representative population-based sample and can be used for research and clinical practice ( 54 ). In our sample, good internal consistency was observed for both the PTSD (α = 0.89) and cPTSD scale (α = 0.87).…”
Section: Methodsmentioning
confidence: 99%
“…The targeting of the six-item PTSD and DSO scales has not previously been investigated. Christen et al ( 2021 ) evaluated item information within the two scales for a representative sample for the German general population; however, it was not related to the distribution of items and persons (i.e. targeting).…”
Section: Discussionmentioning
confidence: 99%
“…for each grouping variable, item difficulties for each items are equal for the subgroups) across the community and clinical sample, and suggested that there was no substantial issue with lack of invariance. The psychometric findings of Cloitre et al ( 2018 ) concerning dimensionality and invariance for the 12-item ITQ were largely replicated in a German study with nationally representative data, also using dichotomized items (Christen et al, 2021 ). The latter study also found no difference in how well the one- and two-parameter models described the PTSD scale, but as for the community sample in Cloitre et al ( 2018 ), suggested that the two-parameter model described the DSO scale better.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations